Herpesviruses dUTPases: A New Family of Pathogen-Associated Molecular Pattern (PAMP) Proteins with Implications for Human Disease - Marshall V. Williams; Brandon Cox; Maria Eugenia Ariza (Pathogens, 2016)
The human herpesviruses are ubiquitous viruses and have a prevalence of over 90% in the adult population. Following a primary infection they establish latency and can be reactivated over a person’s lifetime. While it is well accepted that human herpesviruses are implicated in numerous diseases ranging from dermatological and autoimmune disease to cancer, the role of lytic proteins in the pathophysiology of herpesvirus-associated diseases remains largely understudies. Only recently have we begun to appreciate the importance of lytic proteins produced during reactivation of the virus, in particular the deoxyuridine triphosphate nucleotidohydrolases (dUTPase), as key modulators of the host innate and adaptive immune responses. In this review, we provide evidence from animal and human studies of the Epstein–Barr virus as a prototype, supporting the notion that herpesviruses dUTPases are a family of proteins with unique immunoregulatory functions that can alter the inflammatory microenvironment and thus exacerbate the immune pathology of herpesvirus-related diseases including myalgic encephalomyelitis/chronic fatigue syndrome, autoimmune diseases, and cancer.